The Role of Islamic Jurisprudence in Preserving the Public Funds of the State - Salih , Abdul Ghafoor (Islamic Sciences Journal, 2023)
ABSTRACT Praise be to Allah , the Lord of the world, and prayers and peace be upon our Prophet Al-Hadi, the faithful envoy, as a mercy to the worlds and his family and companions as a whole, and whoever follows his path with charity until the Day of Judgment. This research came under the title (The Role of Islamic Jurisprudence in Preserving the Public Funds of the State), in which I stated that money is the pillar of the economies of all countries in the world . The economy of any country does not go straight unless it has financial resources that run its affairs, laws are legislated to protect them , and their benefits are given to the individuals and society. Therefore, the Islamic Sharia was keen to protect the funds, including the public funds of the state. The jurists explained the legal provisions and mechanisms that preserve the state's public funds, because public funds is more vulnerable to assault than private funds, so it was necessary to explain the seriousness of them attaking them , and the necessity of laying the foundations to protect. As a result The jurists role was in the diligence of putting the mechanisms to save the public money with a clarification of the Sharia ruling.